Desenvolvimento de revestimentos híbridos aplicados aos substratos de Ti-6Al-4V para aplicações biomédicas - Santana, Joseane de Andrade (2019)
The Ti-6Al-4V alloy is one of the most widely used metallic biomaterials due to the corrosion resistance, high static and fatigue strength, relatively low elasticity modulus, low weight, high biocompatibility and direct bone apposition. However, the exposure this alloy to body fluid for a long period of time, has low wear resistance and allows the release of Al and V ions may cause adverse reactions in tissues and neurological disorders. In an attempt to overcome these problems, hybrid Siloxane-PMMA coatings were synthesized by the sol-gel method and deposited by immersion on the surface alloy Ti-6Al-4V treated. Calcium chloride was added to some compositions to facilitate the formation of hydroxyapatite and promote osteosynthesis. At the start, was studied the hybrids formation by means of the FTIR and TG techniques and it was observed that the addition of the calcium salt to the hybrid matrix favored the formation of more regular polymer chains, influenced in hydrolysis and condensation reactions, besides having higher thermal resistance to hybrids. As regards morphological tests, these showed the formation of homogeneous, low thickness, substrate adherent, hydrophilic coatings with some micro-roughness as the molar ratio of calcium salt to the composition was increased. Electrochemical simulated body fluid (SBF) tests at 37 °C and monitored by electrochemical techniques indicated higher corrosion resistance for the hybrid coatings than for the uncoated alloy in the first few hours of immersion, however, the film without addition of salt showed is more resistive during longer immersion time due to the more compact silica network. In vitro bioactivity assays demonstrated that hybrid coatings further the formation of hydroxyapatite in SBF. While viability and cell density using murine osteoblastic MC3T3 cells, demonstrated high cell viability and non-toxic effect for all systems and high cell proliferation for the system without addition of calcium chloride. Finally, the results showed that hybrid coating without calcium chloride effectively improved the bioactivity, biocompatibility and corrosion resistance of Ti-6Al-4V substrates.